2017
DOI: 10.1055/s-0037-1608862
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Embolization for Refractory Bleeding

Abstract: Bleeding is a common and often challenging complication of malignancy. Etiologies of hemorrhage in this patient population vary, and bleeding may present as an acute, life-threatening emergency or a chronic, low-volume blood loss. For patients with advanced malignancies, interventions to manage bleeding must be balanced by the patient's life expectancy and quality of life. As such, minimally invasive procedures such as transarterial embolization are useful therapeutic options in appropriately selected patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
0
7
0
3
Order By: Relevance
“…Research has shown that in the case of malignant tumor hemorrhage the expected survival and quality of life of patients should be considered. Since 1970s, arterial embolization has been used to treat refractory hemorrhage in cancer patients (34). A study has shown that patients with gastric cancer hemorrhage treated by endoscopy are prone to recurrence and re-hemorrhage; at this point, arterial embolization should be considered, which may lead to better efficacy (35).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that in the case of malignant tumor hemorrhage the expected survival and quality of life of patients should be considered. Since 1970s, arterial embolization has been used to treat refractory hemorrhage in cancer patients (34). A study has shown that patients with gastric cancer hemorrhage treated by endoscopy are prone to recurrence and re-hemorrhage; at this point, arterial embolization should be considered, which may lead to better efficacy (35).…”
Section: Discussionmentioning
confidence: 99%
“…With steadily published case reports and review papers, the embolization was improved and its reliability was strengthened. Thereby, the technique was continuously developed and the use of interventional radiology expanded [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because vascularity in this area is highly diversified, it is particularly important to become familiarized with possible disparities and anastomoses. That enables to perform selective catheterization avoiding untargeted occlusion which yield undesirable ischemia [ 19 , 22 ]. According to current findings, the probability of the occurrence of single prostate artery from each pelvic side is 57% and double independent arteries arise from both sidewall occur in 43% of patients [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations